ANALISIS PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Roni Hamdani, Acep; Dahlan, Taufiqulloh; Indriani, Rina; Ansor Karimah, Ayu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
The background of this research is because of the low learning motivation of students. The causes of the low learning motivation of students are the lack of interest in learning, not being diligent in facing assignments, quickly giving up when faced with difficulties. Some of the causes of these problems include because the learning process is still using conventional learning. Therefore, it is necessary to innovate learning models that are in line with current needs and realities. One of the learning models that can be applied is the Problem Based Learning model. This study aims to determine: 1) To find out the concept of the Problem Based Learning model. 2) To find out the condition of students' learning motivation so far based on previous research, 3) To find out the use of Problem Based Learning models has an effect on students' learning motivation. This study uses a qualitative approach with the type of research used is library research. Sources of data obtained from books, journals, articles and publications by collecting several previous studies on the Problem Based Learning model on students' learning motivation. Based on research journals that researchers analyzed, it showed that the Problem Based Learning model had an effect on the learning motivation of elementary school students, judging by the results of students' learning tests in elementary school students' learning motivation had increased. Student learning through the Problem Based Learning model shows an influence, seen from the class that was treated using the Problem Based Learning model, the value was higher than the class that was treated with the conventional model.